2023
DOI: 10.1371/journal.pone.0284354
|View full text |Cite
|
Sign up to set email alerts
|

The effects of short messages encouraging prevention behaviors early in the COVID-19 pandemic

Abstract: Effectively addressing public health crises like the COVID-19 pandemic requires persuading the mass public to change their behavior in significant ways. Many efforts to encourage behavior change–such as public service announcements, social media posts, and billboards–involve short, persuasive appeals, yet the effectiveness of these messages is unclear. Early in the COVID-19 pandemic, we tested whether short messages could increase intentions to comply with public health guidelines. To identify promising messag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…We set ω = 0.003, which indicates that users have much more confidence in their own opinions relative to the opinions of others. This aligns with several studies of persuasion which have found a single message can cause a very small opinion shift in a controlled environment [41][42][43][44]. We use a value for ω less than what is implied in these works as we expect there to be many factors that reduce the persuasive power of social media posts, such as user's not seeing a post at all or scrolling past it without reading it.…”
Section: Resultssupporting
confidence: 57%
“…We set ω = 0.003, which indicates that users have much more confidence in their own opinions relative to the opinions of others. This aligns with several studies of persuasion which have found a single message can cause a very small opinion shift in a controlled environment [41][42][43][44]. We use a value for ω less than what is implied in these works as we expect there to be many factors that reduce the persuasive power of social media posts, such as user's not seeing a post at all or scrolling past it without reading it.…”
Section: Resultssupporting
confidence: 57%